An evaluating study of the role of the United States Information Service libraries in the Philippines - Adler, Alice Cecelia (1969)
The United States Information Service operates three libraries in the Philippines, in Manila, Cebu City and Davao City. The objectives of the USIS libraries are twofold : to disseminate information about the United States, its people and its culture; and to help explain and support specific U.S. foreign policy objectives.